The role of haemodynamic analysis in high flow extracranial to intracranial bypass surgery / Sheau Fung Sia - Sheau, Fung Sia (2012)
Use of computational haemodynamics technology is well described for a number of diverse conditions in medicine including predicting flows in the Circle of Willis, risk of rupture of aneurysms,and optimum endovascular stent placement in the management of vascular pathology. Saphenous vein or radial artery interposition grafts are often used for high flow extracranial intracranial bypass procedures. These bypasses have the potential to supply a considerable volume of cerebral blood flow to the brain. However, longterm patency for specific graft types remains unknown.